Interaction of Metallic Nanoparticles With Biomimetic Lipid Liquid Crystalline Cubic Interfaces - Cardellini, Jacopo; Montis, Costanza; Barbero, Francesco; De Santis, Ilaria; Caselli, Lucrezia; Berti, Debora (Frontiers in Bioengineering and Biotechnology, 2022)
In the past decades, events occurring at the nano-bio interface (i.e., where engineered nanoparticles (NPs) meet biological interfaces such as biomembranes) have been intensively investigated, to address the cytotoxicity of nanomaterials and boost their clinical translation. In this field, lamellar synthetic model membranes have been instrumental to disentangle non-specific interactions between NPs and planar biological interfaces. Much less is known on nano-biointeractions occurring at highly curved biological interfaces, such as cubic membranes. These non-lamellar architectures play a crucial -but far from understood- role in several biological processes and occur in cells as a defence mechanism against bacterial and viral pathologies, including coronaviruses infections. Despite its relevance, the interaction of cubic membranes with nano-sized objects (such as viral pathogens, biological macromolecules and synthetic NPs) remains largely unexplored to date. Here, we address the interaction of model lipid cubic membranes with two prototypical classes of NPs for Nanomedicine, i.e., gold (AuNPs) and silver NPs (AgNPs). To this purpose, we challenged lipid-based cubic membranes, either in the form of dispersed nanoparticles (i.e., cubosomes) or solid-supported layers of nanometric thickness, with citrate-stabilized AuNPs and AgNPs and monitored the interaction combining bulk techniques (UV-visible spectroscopy, Light and Synchrotron Small-Angle X-ray Scattering) with surface methods (Quartz Crystal Microbalance and Confocal Laser Scanning Microscopy). We show that the composition of the metal core of NPs (i.e., Au vs Ag) modulates their adsorption and self-assembly at cubic interfaces, leading to an extensive membrane-induced clustering of AuNPs, while only to a mild adsorption of isolated AgNPs. Such differences mirror opposite effects at the membrane level, where AuNPs induce lipid extraction followed by a fast disruption of the cubic assembly, while AgNPs do not affect the membrane morphology. Finally, we propose an interaction mechanism accounting for the different behaviour of AuNPs and AgNPs at the cubic interface, highlighting a prominent role of NPs’ composition and surface chemistry in the overall interaction mechanism.